RANCANG BANGUN AUTOMATIC CAT LITTER BOX BERBASIS ARDUINO UNO - Rendi Ronaldi; Sumpena Sumpena (JURNAL TEKNOLOGI INDUSTRI, 2019)
A litterbox is an indoor litter and urine collection box for cats or rabbits, ferrets, small dogs and other pets that use such a repository. The existing Litterbox has a weakness in keeping the Litterbox in a clean condition and its maintenance is complicated. So we need a tool to facilitate human activities or to support the busyness of various activities, especially cat caretakers.For that purpose, an "Automatic Cat Litter Box" is created which works like a "closet urinal sensor" which can remove cat litter from the litter box after the cat repositories in the box and throws it into a container that has been coated with plastic and a lid so that the smell of litter does not smell. This Automatic Cat Litter Box uses HC-sr04 Ultrasonic Sensor to detect the presence of a cat that works based on changes in the distance read by the sensor.The HC-sr04 Ultrasonic Sensor can detect objects or objects in the sandy area of the Litterbox by determining the 37cm - 40cm distance range as the "initial_ distance" or the distance where the sensor does not detect an object and if the distance that is read is outside the "initial_ distance" range then it can otherwise the sensor has detected an object. Having three criteria in its working system, the first is when an object detected in the sandy area of the Litterbox is more than 30 seconds with a delay of 10 seconds that has been fulfilled, it is certain that the Automatic Cat Litter Box system will work automatically. Second, if the object is detected for less than 30 seconds, then the Automatic Cat Litter Box system will not work. And thirdly, if the object is detected for more than 30 seconds but with a delay time of less than 10 seconds, the Automatic Cat Litter Box system cannot work or returns to the detection process.Keyword : Litterbox, Automatic Cat Litter Box, Sensor Ultrasonik HC-sr04.